Households Demand for Branded Tea in Southwest, Nigeria - SOWUNMI, Fatai Abiola; AKIN-JACOBS, Funmilayo; AMOO, Zakariyah Olayiwola (International Journal of Sustainable Agricultural Research, 2021)
Tea is an important food drink globally with significant health benefit. However, it consumption is low in Nigeria and sub-Saharan Africa generally. There is dearth of literature on branded tea demand. Hence, household demand for branded tea in southwest, Nigeria was investigated. The study revealed the dominance of Lipton tea among other brands of tea. Demand for herbal tea was higher among older respondents. The study affirmed that the monthly household expenditure share on branded tea in the study area and across the states was low. The monthly household expenditure on complements (sugar, milk and honey) was higher than that of branded teas. The study revealed the influence of price on the expenditure shares of branded teas, its substitutes and complements. Marital status and years of education of respondent influenced the decision to consume branded tea. Expectedly, branded teas exhibited complementary relationships with milk, sugar and honey. The expenditure elasticities of all the branded teas except top tea were positive (normal goods). Improvement in local production and processing of tea locally will bring about its improved consumption. It is recommended that the relevant NGOs should raise the level of awareness on the health benefit of tea which may help to raise the household expenditure on it from the present level. Also, it is imperative for government to put enabling policy in place for tea firms to source tea leaf locally to reduce the price of branded teas as well as create jobs along the tea value chain.